2017
DOI: 10.1002/anie.201703389
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of EGF Receptor Inhibitors That Are Selective for the d746750/T790M/C797S Mutant through Structure‐Based de Novo Design

Abstract: Next-generation epidermal growth factor receptor (EGFR) inhibitors against the d746-750/T790M/C797S mutation were discovered through two-track virtual screening and de novo design. A number of nanomolar inhibitors were identified using 2-aryl-4-aminoquinazoline as the molecular core and the modified binding energy function involving a proper dehydration term, which provides important structural insight into the key principles for high inhibitory activities against the d746-750/T790M/C797S mutant. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 22 publications
0
54
0
Order By: Relevance
“…having an IC 50 value of 0.012 nm.T he same group has reported similar approaches against other kinase targets, including mutant EGFR, [33] GSK3b, [34] p38, [35] and Abl kinase, [36] showing the generality of the approach, at least within this target family.H ere again, novel and potent compounds have resulted from the exercise but de novo design is only part of the overall process.…”
Section: Kurzaufsätzementioning
confidence: 84%
“…having an IC 50 value of 0.012 nm.T he same group has reported similar approaches against other kinase targets, including mutant EGFR, [33] GSK3b, [34] p38, [35] and Abl kinase, [36] showing the generality of the approach, at least within this target family.H ere again, novel and potent compounds have resulted from the exercise but de novo design is only part of the overall process.…”
Section: Kurzaufsätzementioning
confidence: 84%
“…Out of this group, picomolar inhibitors were identified, the best of these ( 6 ; Figure ) having an IC 50 value of 0.012 n m . The same group has reported similar approaches against other kinase targets, including mutant EGFR, GSK3β, p38, and Abl kinase, showing the generality of the approach, at least within this target family. Here again, novel and potent compounds have resulted from the exercise but de novo design is only part of the overall process.…”
Section: Aurora Kinase a Inhibitorsmentioning
confidence: 86%
“…Recently, the 2‐aryl‐4‐aminoquinazoline‐based hit 29 was reported as a fourth‐generation EGFR del746‐750/T790M/C797S triple mutant inhibitor derived from virtual screening and de novo design . The enzymatic assays showed that compound 29 has potent EGFR del746‐750/T790M/C797S kinase inhibitory activity with an IC 50 value of 149 nM.…”
Section: Fourth‐generation Inhibitors Overcoming Egfrc797smentioning
confidence: 99%